2016
DOI: 10.1038/nn.4236
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic NMDA receptor signaling couples Src family kinases to pannexin-1 during excitotoxicity

Abstract: Overactivation of neuronal N-methyl-D-aspartate receptors (NMDARs) causes excitotoxicity and is necessary for neuronal death. In the classical view, these ligand-gated Ca(2+)-permeable ionotropic receptors require co-agonists and membrane depolarization for activation. We report that NMDARs signal during ligand binding without activation of their ion conduction pore. Pharmacological pore block with MK-801, physiological pore block with Mg(2+) or a Ca(2+)-impermeable NMDAR variant prevented NMDAR currents, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
264
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(296 citation statements)
references
References 64 publications
13
264
2
1
Order By: Relevance
“…Beyond structural diversity and PTM effects on canonical NMDAR channel activity, there is also channel-independent NMDAR signaling [10,11]. So-called non-canonical, metabotropic mechanisms may depend on active recruitment of Src kinase [12], but understanding the functional significance of these pathways is only beginning. Overall, NMDAR structural, regulatory and signaling diversity gives rise to an extremely heterogeneous stable of potential NMDAR configurations.…”
Section: Nmdar Properties: the Neuronal Precedentmentioning
confidence: 99%
“…Beyond structural diversity and PTM effects on canonical NMDAR channel activity, there is also channel-independent NMDAR signaling [10,11]. So-called non-canonical, metabotropic mechanisms may depend on active recruitment of Src kinase [12], but understanding the functional significance of these pathways is only beginning. Overall, NMDAR structural, regulatory and signaling diversity gives rise to an extremely heterogeneous stable of potential NMDAR configurations.…”
Section: Nmdar Properties: the Neuronal Precedentmentioning
confidence: 99%
“…This group demonstrated that in cultured hippocampal slices the activation of NMDA receptors by application of exogenous NMDA led to Panx1 channel opening which was associated with increased amplitude and frequency of inter-ictal spiking in the zero extracellular Mg 2+ model of epileptiform-like activity [78]. The study also showed that changes in intracellular Ca 2+ did not play a role in NMDA receptor-mediated activation of Panx1 channel opening; instead, the NMDA receptor-mediated activation of Panx1 channels involved the metabotropic NMDA receptor - Src kinase Panx1 complex signaling, independently of the classical Ca 2+ -permeable NMDA receptors [52, 53]. Figure 2A illustrates the signaling pathway by which Panx1 may regulate neuronal excitability according to these studies [52, 53, 78].…”
Section: Pannexin1 and Epileptic Seizure Activitymentioning
confidence: 99%
“…The study also showed that changes in intracellular Ca 2+ did not play a role in NMDA receptor-mediated activation of Panx1 channel opening; instead, the NMDA receptor-mediated activation of Panx1 channels involved the metabotropic NMDA receptor - Src kinase Panx1 complex signaling, independently of the classical Ca 2+ -permeable NMDA receptors [52, 53]. Figure 2A illustrates the signaling pathway by which Panx1 may regulate neuronal excitability according to these studies [52, 53, 78]. …”
Section: Pannexin1 and Epileptic Seizure Activitymentioning
confidence: 99%
“…However, the targeting of pannexins in therapeutics remains in its infancy, owing in large part to their more recent discovery. In two promising new studies, inhibition of Panx1 channels with carbenoxolone reduced the efficiency of triple-negative breast cancer metastasis to the lungs in a preclinical mouse model, while disrupting the association between NMDA-Src-Panx1 via a TAT-tagged peptide protected against ischemic stroke in adult rats [12,122]. Given that Panx1 phosphorylation by Src has recently been reported to induce channel opening, this particular peptide may also be a useful Panx1 channel inhibitor [122][123][124].…”
Section: Connexin and Pannexin Therapeuticsmentioning
confidence: 99%
“…In two promising new studies, inhibition of Panx1 channels with carbenoxolone reduced the efficiency of triple-negative breast cancer metastasis to the lungs in a preclinical mouse model, while disrupting the association between NMDA-Src-Panx1 via a TAT-tagged peptide protected against ischemic stroke in adult rats [12,122]. Given that Panx1 phosphorylation by Src has recently been reported to induce channel opening, this particular peptide may also be a useful Panx1 channel inhibitor [122][123][124]. In another study, Panx3 ablation inhibited the onset of surgically induced osteoarthritis, raising the possibility that a peptide therapeutic specifically inhibiting Panx3 channels may provide treatment for a poorly controlled disease [125,126].…”
Section: Connexin and Pannexin Therapeuticsmentioning
confidence: 99%